Self-efficacy and impostor syndrome in graduate students: a portrayal of covid-19 pandemic - Ogeda, Clarissa Maria Marques [UNESP]; Adurens, Fernanda Delai Lucas [UNESP]; Pedro, Ketilin Mayra (Universidade Federal do Paraná, 2022)
The social isolation recommended by the World Health Organization, during the COVID-19 pandemic, can raise levels of anxiety and stress in students, which affect their productivity. This study aimed to evaluate the levels of self-efficacy and the Impostor Syndrome in stricto sensu graduate students, in the context of the COVID-19 pandemic. It was a quantitative study that had as participants a convenience sample comprised of 200 stricto sensu graduate students. The participants answered an online form that included a sociodemographic questionnaire, the Clance Impostor Phenomenon Scale, and the Self-efficacy Scale in higher education. It was verified that the two scales presented statistically significant and inversely proportional correlation, that is, the higher the levels of Self-efficacy, the lower the levels of Impostor Syndrome. Postgraduates, in relation to Self-efficacy, assessed themselves at high to higher levels, mostly. In turn, in Impostor Syndrome, the respondents evaluated themselves at high or moderate levels.
Autoeficácia e síndrome do impostor em pós-graduandos: um retrato da pandemia da covid-19
Keywords: COVID-19; graduate studies; self-efficacy. impostor syndrome